The Potential Use of Exosomes in Anti-Cancer Effect Induced by Polarized Macrophages - Chizumi Abe; Maharshi Bhaswant; Teruo Miyazawa; Taiki Miyazawa (MDPI AG, 2023)
The rapid development of aberrant cells outgrowing their normal bounds, which can subsequently infect other body parts and spread to other organs-a process known as metastasis-is one of the significant characteristics of cancer. The main reason why cancer patients die is because of widespread metastases. This abnormal cell proliferation varies in cancers of over a hundred types, and their response to treatment can vary substantially. Several anti-cancer drugs have been discovered to treat various tumors, yet they still have harmful side-effects. Finding novel, highly efficient targeted therapies based on modifications in the molecular biology of tumor cells is essential to reduce the indiscriminate destruction of healthy cells. Exosomes, an extracellular vesicle, are promising as a drug carrier for cancer therapy due to their good tolerance in the body. In addition, the tumor microenvironment is a potential target to regulate in cancer treatment. Therefore, macrophages are polarized toward M1 and M2 phenotypes, which are involved in cancer proliferation and are malignant. It is evident from recent studies that controlled macrophage polarization might contribute to cancer treatment, by the direct way of using miRNA. This review provides an insight into the potential use of exosomes to develop an 'indirect', more natural, and harmless cancer treatment through regulating macrophage polarization.